Ghana : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1999)
This Selected Issues paper reviews public service reform in Ghana. The paper highlights that a range of public service reform initiatives have been undertaken in Ghana since the early 1980s. The public service in Ghana is composed of centrally managed agencies, ministries, subvented agencies, district assemblies, and state enterprises. The civil service, which covers the centrally managed agencies, ministries, and local government, accounts for only about 20 percent of total public sector employment as a result of the spin-off in the 1980s of the internal revenue, customs, education, and health services as subvented agencies.